PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN EFEKTIVITAS MANAJEMEN BERBASIS SEKOLAH DI SD NEGERI 2 PEDUNGAN - Chindytia; Anak Agung Gede Agung; Wijayanti, Ni Made Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of the principal’s leadership in the implementation of School-Based Management (SBM) at SD Negeri 2 Pedungan. The study employed a qualitative approach with a case study design. Data were collected through observations, interviews, and documentation involving the principal, teachers, educational staff, school committees, and related stakeholders. Data analysis was conducted using descriptive qualitative techniques through data reduction, data presentation, and conclusion drawing, supported by SWOT analysis. The results showed that the implementation of SBM at SD Negeri 2 Pedungan was categorized as very good. The principal demonstrated visionary, participatory, and transparent leadership in managing the school. Management functions such as planning, organizing, supervision, monitoring, and evaluation were implemented effectively and continuously. In addition, the utilization of technology-based facilities and infrastructure supported the improvement of learning quality. However, collaboration with external institutions and socio-religious organizations still needs to be improved so that the implementation of SBM can run more optimally and sustainably.